Sexual selection and population divergence III: Interspecific and intraspecific variation in mating signals. (27th April 2020) - Moran, Peter A.; Hunt, John; Mitchell, Christopher; Ritchie, Michael G.; Bailey, Nathan W.
Abstract: A major challenge for studying the role of sexual selection in divergence and speciation is understanding the relative influence of different sexually selected signals on those processes in both intra‐ and interspecific contexts. Different signals may be more or less susceptible to co‐option for species identification depending on the balance of sexual and ecological selection acting upon them. To examine this, we tested three predictions to explain geographic variation in long‐ versus short‐range sexual signals across a 3, 500 + km transect of two related Australian field cricket species ( Teleogryllus spp.): (a) selection for species recognition, (b) environmental adaptation and (c) stochastic divergence. We measured male calling song and male and female cuticular hydrocarbons (CHCs) in offspring derived from wild populations, reared under common garden conditions. Song clearly differentiated the species, and no hybrids were observed suggesting that hybridization is rare or absent. Spatial variation in song was not predicted by geography, genetics or climatic factors in either species. In contrast, CHC divergence was strongly associated with an environmental gradient supporting the idea that the climatic environment selects more directly upon these chemical signals. In light of recently advocated models of diversification via ecological selection on secondary sexual traits, the different environmental associations we found for song and CHCs suggest that the impact of ecological selection on population divergence, and how that influences speciation, might be different for acoustic versus chemical signals. Abstract : The strength and form of selection imposed on multi‐modal sexual signal components may differ. Here, we examined geographic variation in calling song and cuticular hydrocarbons across an extensive transect of a classic Australian field cricket study system. Spatial variation in song was not predicted by geography, genetics or climatic factors in either species. In contrast, CHC divergence was strongly associated with an environmental gradient supporting the idea that the climatic environment selects more directly upon these chemical signals.